Why does formalism exist in local environmental rectification? A qualitative comparative analysis based on Central Environmental Protection Inspection cases - Zhou Lu; Limin Gao; Jing Wu; Xiaodong Li (PLoS ONE, 2025)
China’s Central Environmental Protection Inspection (CEPI) has achieved significant results, with 287,000 public reports received by June 2022, facilitating the resolution of numerous environmental issues; however, formalism persists in some regions during environmental rectification efforts. Existing research lacks sufficient explanations for the diverse driving paths underlying local formalism. This paper selects 20 typical CEPI cases from northern, central, eastern, southern, northwestern, and southwestern China. Guided by the Technology-Organization-Environment (TOE) framework, it employs the crisp-set Qualitative Comparative Analysis (csQCA) method to identify the diversified pathways of local formalism. The results indicate that: (1) Local formalism is influenced by technological, organizational, and environmental factors, including environmental facility constraints, digital facility constraints, accountability pressure, attention constraints, economic constraints, and industrial constraints; (2) No single condition constitutes a necessary cause of formalism in local environmental rectification; instead, it arises from the interaction of multiple conditions; (3) The three paths classified by nine conditional configurations, namely technology-environment path, technology-organization path, and organization path, are the primary paths for local formalism. (4) Environmental infrastructure constraints, attention constraints, accountability pressure, and industrial constraints serve as core conditions across all pathways, with accountability pressure playing a particularly significant role. This paper offers insights into mitigating formalism in local environmental rectification.